Peran Moderasi Etika Konsumsi Islam pada Pengaruh Green Marketing, Ethnosentrisme Konsumen, dan Gaya Hidup Halal Terhadap Keputusan Pembelian Kosmetik - Novita, Yeyen; Pratama, Abdul Aziz Nugraha (Ekonomis: Journal of Economics and Business, 2024)
This study aims to determine and analyze the effect of Green Marketing, Consumer Ethnocentrism and Halal Lifestyle on Purchasing Decisions with Islamic Consumption Ethics as a moderating variable (Study on Wardah Cosmetics Consumers). In this study using quantitative methods by processing primary data obtained through distributing questionnaires to consumers of Wardah cosmetics. The samples taken were 462 respondents with purposive sampling technique. Then the results obtained were processed with IBM SPSS version 22. The analysis used included instrument tests, statistical tests, classical assumption tests and Moderate Regression Analysis (MRA). The results of this study indicate that green marketing does not significantly influence the increase in purchasing decision variables. Consumer ethnocentrism has a significant effect on increasing purchasing decision variables. The halal lifestyle has a significant effect on increasing the purchasing decision variable. Islamic consumption ethics significantly influence the increase in purchasing decision variables. Islamic consumption ethics is not able to moderate the relationship between green marketing variables, consumer ethnocentrism and halal lifestyle and purchasing decisions.